Study of circuit performance and non quasi static effect in germanium tunnel FET for different temperatures. (August 2019) - Ghosh, Sayani; Koley, Kalyan; Sarkar, Chandan K.
Abstract: Recent days, for low power applications, germanium (Ge) is considered to be a good alternative of Silicon (Si) as channel material for TFETs to boost the on current. This study reports on the reliability of Ge-pTFET in presence of temperature variability. The reliability is studied through comparative analysis of Analog and Small-signal parameters. The variation in lattice temperature is a crucial issue for reliability of any device since it modulates the band gap narrowing at the tunneling junctions and hence tunneling characteristics of the device. In this work, the impact of temperature variation is systematically analyzed in Ge-pTFET in terms of Non-Quasi-static small-signal-model parameters along with Analog Figure-of-Merits. Also, linearity performance is investigated by means of IIP3 and 1-dB compression point for the variation of temperature, ranges from 200 K to 400 K. Finally, the impact of temperature variation is analyzed in mixed mode circuit simulations for the applications of cascode amplifier circuit and common source amplifier circuit.